Deviation of habitat salinity during seasonal gonad recrudescence affects plasma sex steroid levels and suppresses gonadal maturation in an euryhaline fish Etroplus suratensis. (26th June 2017) - Mandal, Babita; Sawant, Paramita Banerjee; Dasgupta, Subrata; Chadha, Narinder Kumar; Sundaray, Jitendra Kumar; Sawant, Bhawesh T; Bera, Aritra
Abstract: Impact of osmoregulation on plasma sex steroid levels and gonadal histo‐architecture was monitored to elucidate the effects of deviation from habitat salinity on gonadal recrudescence in an active reproductive season of an euryhaline fish Etroplus suratensis (pearlspot). Fish were maintained in three different salinities of 0 ppt Fresh Water (FW), 15 ppt Brackish Water (BW) and 30 ppt Sea Water (SW) for a period of 60 days. Plasma osmolality values were found to be significantly highest in SW‐acclimated fish accompanied by highest levels of plasma K⁺ and Cl¯ ions. The progress of gonadal recrudescence was higher in BW followed by FW and SW as evident from the cellular features of gonads and increased level of plasma sex steroids, such as, in case of female and 11‐keto Testosterone and Testosterone in case of males. Plasma cortisol levels were comparatively higher in fish of both sexes in SW group. Significantly high levels of cortisol in SW suggest its role in hypo‐osmoregulation and associated stress. This study clearly reveals that salinity changes during the active reproductive phase can suppress the steroid‐mediated gonad recrudescence maximally under hypo‐osmoregulation in an euryhaline fish.